Braitenberg Vehicles as Computational Tools for Research in Neuroscience - Shaikh, Danish; Rañó, Ignacio (Frontiers in Bioengineering and Biotechnology, 2020)
Valentino Braitenberg reported his seminal thought experiment in 1984 using reactive automatons or vehicles with relatively simple sensorimotor connections as models for seemingly complex cognitive processes in biological brains. Braitenberg’s work, meant as a metaphor for biological life encompassed a deep knowledge of and served as an analogy for the multitude of neural processes and pathways that underlie animal behaviour, suggesting that seemingly complex behaviour may arise from relatively simple designs. Braitenberg vehicles have been adopted in robotics and artificial life research for sensor-driven navigation behaviours in robots such as localising sound and chemical sources, orienting towards or away from current flow under water etc. The neuroscience community has benefitted from applying Braitenberg’s bottom-up approach towards understanding analogous neural mechanisms underpinning his models of animal behaviour. We present a summary of the latest studies of Braitenberg vehicles for bio-inspired navigation and relate the results to experimental findings on the neural basis of navigation behaviour in animals. Based on these studies, we motivate the important role of Braitenberg vehicles as computational tools to inform research in behavioural neuroscience.